If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -62 = 8(2x + 3) + -11 Reorder the terms: -62 + x = 8(2x + 3) + -11 Reorder the terms: -62 + x = 8(3 + 2x) + -11 -62 + x = (3 * 8 + 2x * 8) + -11 -62 + x = (24 + 16x) + -11 Reorder the terms: -62 + x = 24 + -11 + 16x Combine like terms: 24 + -11 = 13 -62 + x = 13 + 16x Solving -62 + x = 13 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. -62 + x + -16x = 13 + 16x + -16x Combine like terms: x + -16x = -15x -62 + -15x = 13 + 16x + -16x Combine like terms: 16x + -16x = 0 -62 + -15x = 13 + 0 -62 + -15x = 13 Add '62' to each side of the equation. -62 + 62 + -15x = 13 + 62 Combine like terms: -62 + 62 = 0 0 + -15x = 13 + 62 -15x = 13 + 62 Combine like terms: 13 + 62 = 75 -15x = 75 Divide each side by '-15'. x = -5 Simplifying x = -5
| 4b+5=41 | | 0.833333333s+0.222222222=0.5833333 | | 42x+5=7 | | 1/3x-3=10 | | 5(-3x+5)-4y=-3 | | f(x)=2x*2+4x-7 | | 4n^2+34n+72=0 | | 600=0.25x | | 200=40y-2y^2 | | 10(-8x-7)-(6x+4)=98 | | 10n^2+79n-8=0 | | -3(-6w+7)-3w=3(w-9)-2 | | 82=3(v+7)-2 | | 12=3+3r | | f(x)=x*2+6x+3 | | 8x+7=5x+8 | | f(6x)=100-200x | | x+36=-51 | | 3=-9x+12 | | 5x^2+20x-55=0 | | 6-2r=-94 | | 0.666666667x+5=2.5 | | x^2+x^2+14x+49=1225 | | f(x)=2x-x*2+3 | | 8(7+6n)+2(9-7n)=40 | | 5=2-×/3 | | 1800=120y-2y^2 | | -9=-3+4x | | 2X+6=3X-13 | | 5m-2/2 | | 3/28b=9/4 | | 1800=120y-y^2 |